Prevalence, bacterial profile, antimicrobial susceptibility patterns and associated risk factors of bacterial UTI among diabetic patients at Jigjiga University Sheik Hasan Yabare Comprehensive Specialized Hospital, Jigjiga, Eastern Ethiopia - Bawlah Tahir; Niman Tayib; Abdi Hassen Ahmed; Daniel Tolossa; Surafel Mekuria; Shamil Barsenga; Kader Muse; Sara Tesfaye; Addisu Tesfaye; Fasil Getu; Abdurahman Kedir Roble; Abdirizak Mahdi; et al. (BMC Infectious Diseases)
Abstract Background Diabetic Mellitus (DM) is a chronic condition characterized with higher blood glucose due to lack of insulin production, or the body cannot effectively use insulin. Bacterial urinary tract infections (UTIs) remains one of the common public health crises in diabetic patients worldwide. Diabetic patients are at a high risk of developing UTIs. In addition, the emergence of rapid drug resistance nowadays poses a great public health threat in management of bacterial UTIs in diabetic patients worldwide. Objective To assess the prevalence, bacterial profile, antimicrobial susceptibility pattern and associated risk factors of bacterial UTI among Diabetic patients at Jigjiga University Sheik Hasan Yabare Comprehensive Specialized Hospital, Jigjiga Eastern Ethiopia from February 20, to April 30, 2024. Methods Institution-based cross-sectional study was conducted from February 20, to April 30, 2024. Total of 220 study participants were recruited. Clean catch mid-stream urine was collected and was inoculated onto MacConkey agar and Blood agar. Bacterial identification was carried out based on standard protocol. Antibiotic susceptibility testing was done by Kirby Baurer disc diffusion method. The data were entered into Epi-data version 4.6, exported to and analyzed in SPSS version 25. Bivariate and multivariable logistic regression analysis was performed to measure the association. P-value ≤ 0.05 was considered statistically significant. Result The overall prevalence of significant bacteriuria among Diabetic patients was 10.5% (23/220, 95%CI: 6.4 – 14.6%). Of these, 82.6% (19/23) were gram negative bacteria. E. coli was the most isolated uropathogens constituting 65.2% (15/23) followed by S. epidermis, 8.7% (2/23). Duration of DM, history of hypertension and being symptomatic for UTI at the present were statistically associated with significant bacteriuria. Gram negative uropathogens were highly susceptible to nitrofurantoin (94.7%), amikacin (84.2%) and tobramycin (68.4%). Gram positive isolates were 100% susceptible to nitrofurantoin and gentamicin. The overall proportion of Multi-drug resistance among the bacterial isolates was 60.9% (14/23, 95%CI; 54.5—67.3%). Conclusion An identification of higher rate Multi-drug resistant uropathogens necessitates proper care of antibiotic selection for prescription and enhancing microbiological testing coverage in the low-income settings.